Phantom Limbs: South Indian Dance and Immigrant Reifications of the Female Body - Kalpana Ram (Journal of Intercultural Studies Vol. 26, Nos. 1/2, February/May 2005, pp. 121/137, 2005)
This paper explores the phenomenology of migration and gender, seeking to understand how it is that a certain construction of `Indianness' and of womanhood finds one form of expression in the enrolment of middle-class girls in south Indian and other `classical' dance schools. The paper argues that the immigrant situation recalls and opens up to be retrieved, an earlier history of nationalism. It does so, not in the form of intellectual recall, but because the structure of affect in the immigrant present resembles an earlier crisis of the emergent middle class under British colonialism. In this situation, the patriarchal universe of the immigrant requires wives and daughters to magically function as phantom limbs, providing an unstable and illusory impression of continuing to enjoy a grip on the world. The paper interrogates this impression from the perspective of young Indian women deeply involved in Indian dance.